2014
DOI: 10.1080/13554794.2014.919325
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of implicit emotional recognition in posterior cortical atrophy (PCA)

Abstract: Previous single-case reports in posterior cortical atrophy (PCA) have shown preserved nonconscious visual recognition despite the absence of explicit recognition. In this study, we investigated three levels of visual recognition in both a female patient with PCA and a control group during the presentation of neutral, positive, and negative affective stimuli. Our results confirmed the profile of impaired explicit recognition and intact psychophysiological responses in the patient. In addition, she was able to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…10 In 2015, a report was presented on a woman with PCA who, despite showing decreased explicit visual recognition, retained some implicit awareness of image-associated valence and arousal. 9 We confirmed the relative preservation of FE recognition vs the recognition of FI among patients with PCA, which demonstrated that the difference between these 2 abilities was greater in patients with PCA than in patients with AD or patients with bvFTD. Although the ability to recognize facial identities was lower in patients with PCA than in any other group, the ability to recognize FE did not differ from other patients with dementia, including AD or bvFTD.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…10 In 2015, a report was presented on a woman with PCA who, despite showing decreased explicit visual recognition, retained some implicit awareness of image-associated valence and arousal. 9 We confirmed the relative preservation of FE recognition vs the recognition of FI among patients with PCA, which demonstrated that the difference between these 2 abilities was greater in patients with PCA than in patients with AD or patients with bvFTD. Although the ability to recognize facial identities was lower in patients with PCA than in any other group, the ability to recognize FE did not differ from other patients with dementia, including AD or bvFTD.…”
Section: Discussionsupporting
confidence: 73%
“…8 Given the presumptive preservation of these pathways in PCA, despite the degeneration of cortical networks for visual processing, single case studies have suggested that recognition of emotionally salient stimuli may be preserved in PCA as in cortically blind patients. 9,10 Herein, we hypothesized that FE recognition would be relatively preserved in PCA (i.e., similar to other groups), compared to both facial identity (FI) recognition and other tests of visual function.…”
mentioning
confidence: 98%